Effects of life stage on eDNA detection of the invasive European green crab (Carcinus maenas) in estuarine systems - Laura C. Crane (Elsevier, 2021)
Early and efficient detection of rare and invasive species is critical for the effective management of their populations. Environmental DNA (eDNA) detection techniques have been used for monitoring soft-bodied organisms (e.g., fishes) and some invertebrates, primarily in freshwater systems, but there are limited examples of eDNA as a method for monitoring marine crustaceans. The present study evaluates the efficacy of applying eDNA methods for detecting the invasive European green crab (Carcinus maenas) in a dynamic estuarine environment, and the effect of crab life stage (sex, molt stage, ovigery, abundance) on eDNA detection rates. An initial field experiment conducted in a local salt marsh system detected no C. maenas eDNA in sediment samples associated with traps containing C. maenas. In subsequent laboratory trials, aquaria containing one or two C. maenas at different life stages (soft-shell, hard-shell, male, female, ovigerous) were evaluated in replicated treatments to test the hypothesis that C. maenas exudes eDNA at higher levels when ovigerous, soft-shell, or at higher abundances. Duplicate sediment slurry and water samples were collected from each aquarium (n = 23) prior to crab addition (T-0), and after 24 h (T-1), 4 days (T-2), and 7 days (T-3). Sediment slurry and water samples were filtered, extracted, and analyzed using a species-specific droplet digital PCR (ddPCR) assay. In all non-control aquaria, C. maenas eDNA was detected, but concentrations were low (<10 copies/µL) in non-ovigerous treatments. eDNA concentrations were significantly higher in sediment slurry versus water samples for male and ovigerous treatments. Overall, concentrations increased from T-0 to T-1 but did not significantly change from T-1 through T-3. The findings from this study indicate that during most of their life cycle, C. maenas shed low levels of DNA, highlighting the importance of considering life stage and sampling methodology when using eDNA to monitor crustaceans in estuarine environments.